Impact of age on cytotoxic-induced ovarian failure in breast cancer treated with adjuvant chemotherapy and triptorelin. (March 2016) - Meattini, Icro; Saieva, Calogero; Meacci, Fiammetta; Scotti, Vieri; De Luca Cardillo, Carla; Desideri, Isacco; Baldazzi, Valentina; Mangoni, Monica; Scoccianti, Silvia; Detti, Beatrice; Simontacchi, Gabriele; Nori, Jacopo; et al.
Aim: This study analyzes our single-center, retrospective experience on 63 premenopausal breast cancer patients treated with monthly triptorelin and concomitant chemotherapy.Patients & methods: Concomitant chemotherapy and triptorelin were adopted as part of premature ovarian failure prevention strategy.Results: Age at diagnosis was the main factor influencing fertility preservation (p = 0.002). Compared with patients aged 41–45 years, the probability of menses resumption was almost threefold than for women aged 35–40 years, and significantly higher for women aged <35 years (hazard ratio: 9.0; p = 0.0001). The cumulative proportion among patients who resumed menses was 33.3% at 6 months, 75% at 12 months and 87.5% at 24 months. Seven patients attempted pregnancy, and five (71%) obtained healthy deliveries.Conclusion: We observed an acceptable rate of fertility preservation. Age at diagnosis influences fertility preservation.